IMPLEMENTASI PERJANJIAN INTERNASIONAL PENYIMPANAN JASAD RENIK UNTUK KEPENTINGAN PROSEDUR PATEN (Studi Pada Kementerian Hukum dan HAM Provinsi Lampung) - Recca Ayu Hapsari; Aprinisa; Dera Maulinda (LPPM STIH Awang Long, 2023)
Every human activity experiences a significant shift as a result of the passage of time, especially in the field of technology. Technological advances will have a positive effect on the economy from year to year, especially in the technology sector. The purpose of this research is to find out how the implementation of international recognition for storing micro-organisms of the Director General of Ki, Ministry of Law and Human Rights Regional Office of Lampung Province and the form of legal protection for patent applications related to microorganisms. Intellectual Property Rights (IPR) are rights to things that originate from the work of the brain and reason or reason regarding the work of the human ratio. These rights are referred to as property rights. The results of his work in the form of immaterial objects (ie objects that are not tangible). The approach taken is normative juridical, namely using legal principles and comparative law to investigate literary data or secondary information.